Effect of Neuromuscular Electrical Stimulation After Total Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Peng, Linbo; Wang, Kexin; Zeng, Yi; Wu, Yuangang; Si, Haibo; Shen, Bin (Frontiers in Medicine, 2021)
Background: This systematic review and meta-analysis aimed to evaluate the effect of neuromuscular electrical stimulation (NMES) on quadriceps muscle strength, pain, and function outcomes following total knee arthroplasty (TKA). Methods: PubMed/Medline, Embase, Web of Science, CENTRAL, Scopus, PsycINFO, PEDro, CINAHL, CNKI, and Wanfang were systematically searched for RCTs from their inception to 18 June 2021. Results: Nine RCTs that involving 691 patients were included in the meta-analysis. Our pooled analysis showed that NMES improved quadriceps muscle strength after TKA within 1 months (SMD: 0.81; 95%CI: 0.51 to 1.11), 1-2 months (SMD: 0.55; 95%CI: 0.13 to 0.97), 3-4 months (SMD: 0.42; 95%CI: 0.18 to 0.66), and 12-13 months (SMD: 0.46; 95%CI: 0.18 to 0.74), pain between 1-2 months (MD: -0.62; 95%CI: -1.04 to -0.19), WOMAC between 3-4 months (MD: -0.43; 95%CI: -0.82 to -0.05), TUG within 1 month (MD: -2.23; 95%CI: -3.40 to -1.07), 3MWT between 3-6 months (MD: 28.35; 95%CI: 14.55 to 42.15), and SF-36 MCS between 3-6 months after TKA (MD: 4.20, 95%CI: 2.41 to 5.98). Conclusion: As a supplementary treatment after TKA, postoperative NMES could improve the short-term to long-term quadriceps muscle strength, mid-term pain, and mid-term function following TKA. However, many outcomes failed to achieve statistically meaningful changes and minimal clinically important diference (MCID), thus the clinical benefits remained to be confirmed.